Interaksi Simbolis Masyarakat Dalam Memaknai Kesenian Jathilan - Noor Haliemah; Rama Kertamukti (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2017)
This research aims to explain how symbolic interaction of people in interpreting Jathilan art in Padukuhan Mendak Desa Girisekar. Kecamatan Panggang, Kabupaten Gunung Kidul. This research uses qualitative descriptive method. Data were collected using observation, in-depth interview and documentation. To check validity of data, the researcher uses triangulation of sources. The result shows that people interpret Jathilan art through verbal and non-verbal communication carried by Jathilan artists, within each performance or in everyday life. Verbal and non-verbal communication have been done by Jathilan artists through elements contained in Jathilan art including form of motion, costumes, properties and music. People can interpret Jathilan art because they regularly watch the show of Jathilan. In addition, the values contained in Jathilan art have been delivered to public through socialization as the first step so that values embodied in Jathilan art can be interpreted and implied by people in their life.